Utilisation of the advance health directive among older Australian rural adults: a qualitative study. Issue 2 (1st June 2012) - Sinclair, C; Auret, K; Forrester, L; Knight, A; Burgess, A; Bulsara, C
Abstract : Advance care planning (ACP) facilitates communication of an individual's treatment wishes to their family and medical staff. Research suggests this process is beneficial, however community uptake of ACP, and its associated legal documentation, has been slow. Prochaska's transtheoretical model explains the process of engaging with health behaviours, proposing discrete stages of readiness (precontemplation, contemplation, preparation, action and maintenance). Applying this model in the ACP context suggests that an individual's perceived susceptibility and empowerment will influence transition towards the behaviour. We used qualitative methods to investigate factors influencing uptake of the newly legislated Advance Health Directive (AHD) among older adults in rural Western Australia. Interviews were conducted with 61 older adults, recruited from different sectors of the community for variation in individual levels of perceived susceptibility and empowerment. Participant responses indicated moderate levels of awareness of the AHD, and general community support for the document, however this did not predict the individual's personal stage of readiness to engage in ACP. Factors associated with the individual's level of perceived susceptibility (e.g. personal/family health scares, past experience with close others in end of life care, physician prompting) were associated with transition through the earlier stages of the model. Factors associated with the individual's level of empowerment (e.g. cognitive capacity, support from physician and family) were associated with transition through later stages of the model. A number of factors which boosted susceptibility also lowered empowerment (e.g. health scares and absence of physician or family support) suggesting the importance of timely prompting of ACP.